The lactate dehydrogenase gene is involved in the growth and metabolism of Lacticaseibacillus paracasei and the production of fermented milk flavor substances - Sichang Fang; Xin Song; Liru Cui; Jinping Bai; Han Lu; Shijie Wang (Frontiers in Microbiology, 2023)
ObjectiveLactate dehydrogenase (ldh) in lactic acid bacteria is an important enzyme that is involved in the process of milk fermentation. This study aimed to explore the changes and effects of fermented milk metabolites in mutant strains after knocking out the ldh gene of Lacticaseibacillus paracasei.MethodsThe ldh mutant ΔAF91_07315 was obtained from L. paracasei using clustered regularly interspaced short palindromic repeats technology, and we determined fermented milk pH, titratable acidity, viable count, and differential metabolites in the different stages of milk fermentation that were identified using metabolomic analysis.ResultsThe results showed that the growth rate and acidification ability of the mutant strain were lower than those of the wild-type strain before the end of fermentation, and analysis of the differential metabolites showed that lactate, L-cysteine, proline, and intermediate metabolites of phenylalanine, tryptophan, and methionine were downregulated (P < 0.05), which affected the growth initiation rate and acidification ability of the strain. At the end of fermentation (pH 4.5), the fermentation time of the mutant strain was prolonged and all differential metabolites were upregulated (P < 0.05), including amino acids and precursors, acetyl coenzyme A, and other metabolites involved in amino acid and fatty acid synthesis, which are associated with the regulation of fermented milk flavors. In addition, riboflavin was upregulated to promote the growth of the strain and compensate for the growth defects caused by the mutation.ConclusionOur data established a link between the AF91_07315 gene and strain growth and metabolism and provided a target for the regulation of fermented milk flavor substances.